2007
DOI: 10.1152/ajpgi.00273.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induced NF-κB activation protects against cell injury in cultured rat gastric mucosal epithelium

Abstract: Mustonen H, Hietaranta A, Puolakkainen P, Kemppainen E, Paimela H, Kiviluoto T, Kivilaakso E. Ethanol induced NF-B activation protects against cell injury in cultured rat gastric mucosal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Indeed, ethanol has been reported to regulate the activity of many transcription factors (17, 18, 36 -39). For example, ethanol has been shown to reduce or increase the binding activity of NF-B to an NF-B oligonucleotide probe in rat pancreatic acinar cells (36) and gastric mucosal epithelia, respectively (37). In addition, it has been suggested that ethanol increases the activity of transcription factors and STAT3, specificity protein-1 (Sp1), and AP1, thereby up-regulating IL-10 expression in human monocytes (38).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ethanol has been reported to regulate the activity of many transcription factors (17, 18, 36 -39). For example, ethanol has been shown to reduce or increase the binding activity of NF-B to an NF-B oligonucleotide probe in rat pancreatic acinar cells (36) and gastric mucosal epithelia, respectively (37). In addition, it has been suggested that ethanol increases the activity of transcription factors and STAT3, specificity protein-1 (Sp1), and AP1, thereby up-regulating IL-10 expression in human monocytes (38).…”
Section: Discussionmentioning
confidence: 99%
“…Positive controls were obtained by transfecting the cells with Lamin A/C siRNA (100 nM, D-001050-01-05, Dharmacon, Lafayette,CO) and following the Lamin A/C expression in these cells. The effect of relA siRNA transfections on relA protein expression is given in [2].…”
Section: Caspase-3 Assaymentioning
confidence: 99%
“…We have recently shown that exposure to modest concentrations of ethanol (EtOH) induces transcription factor nuclear factor-jB (NF-jB) activation in gastric surface epithelial cells. Inhibition of this activation led to increased apoptotic activity, suggesting that NF-jB defends the epithelium against EtOH insult [1,2]. It is not known whether other ulcerogenic agents, such as bile acids or acetylsalicylic acid (ASA), exert a similar protective action in gastric surface epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study in vitro has shown that ethanol exposure induced moderately Cox-2 expression in the rat gastric mucosal cell line cells (Mustonen et al, 2007). Here, we not observed difference of the ciclooxygenase-2 expression between the ethanol treated-groups and the respective control groups.…”
Section: Discussioncontrasting
confidence: 67%